Penanganan Spesimen Jaringan Dan Sitologi Pada Tahap Preanalitik - Wresnindyatsih (Fakultas Kedokteran Universitas Sriwijaya, 2019)
Anatomical Pathology Examination is an examination of specimens from the results of operations and or other medical proceeding on patients. This examination is carried out to establish a diagnosis of a disease. The stages of specimen handling are interrelated with one another. This will affect the accuracy of the pathology diagnosis. In the molecular era specimen handling is becoming increasingly important and must be done carefully according to established standards. The purpose of this review is to discuss the standard procedures for the preanalytic stage of specimen handling before examining in the Anatomy Pathology Laboratory.